Analysis of the Influence of Marketing MIX on Factors of Buying Behaviour of Acne Skincare in Yogyakarta - Erza Ridha Kartika; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
The development of skin care in Indonesia is currently proliferating. Cosmetics for treating acne are one of the fastest growing markets in skincare. This study aims to identify acne skincare product brands in carrying out marketing strategies using the marketing mix method that influences consumer purchasing behaviour factors in Yogyakarta. This research is cross-sectional, with consumers interviewed using a structured questionnaire with a Likert scale system. Consumption patterns investigated in this survey include product brand, price, place and promotion. This survey involved 400 consumer respondents, the majority of whom were female (68.2%), on average aged 20-29 years (62.1%), were students (58%), with income <Rp. 500,000/month ( 41.8%). The average yield value for each marketing mix variable starts with the product variable with a score of (44.37, SD 7.99) followed by the price and promotion variables with an average score of each (34.82) and ( 25.89) which has the most influence on purchasing behaviour factors for acne skincare products. Meanwhile, the place variable obtained the lowest average score (16.8, SD 3.848). The results of the analysis of the influence of marketing mix variables on purchasing behaviour factors can be concluded that product and promotion variables influence purchasing behaviour factors with values of 10, 421 and 5.386, which have deals greater than the t-table values obtained at 2.24.